Clarifying Concepts Of Knowledge And Information - Literature Review - Ahenkorah-Marfo, Michael (Journal of Knowledge Management Practice, 2012)
This paper analyzes the concepts of information and knowledge constructively, clarifying the confusion between the two concepts in the literature. It does this by reviewing the literature available from notable authors in the knowledge management literature using arguments and counter arguments before arriving at logical conclusions. It concludes that knowledge and information are of same kind but exist separately with similarities and differences. These similarities and differences are clearly outlined.